Inferior peroneal retinaculum tear with isolated peroneus longus tendon dislocation: A case report of an extremely rare injury, with the proposal of an innovative repair technique - Nicola Mondanelli, MD, PhD; Giacomo Peri, MD; Nicolò Nuvoli, MD; Elisa Troiano, MD; Pietro Aiuto, MD; Carlo Cataldi, MD; Michele Losco, MD, PhD; Stefano Giannotti, MD (Foot & Ankle Surgery: Techniques, Reports & Cases, 2021)
Peroneus longus tendon (PLT) dislocation associated with inferior peroneal retinaculum (IPR) tear is an extremely rare injury. Only 6 cases are described in English literature to date, and its diagnosis is always delayed from the initial trauma. Swelling at the lateral face of the heel and a snapping during the movement of the foot and ankle are typical signs that can induce the suspect of this injury. Operative treatment is required as it typically affects young adults with high functional demands and tendon instability causes pain and functional limitation; also, a neglected dislocated or instable PTL may eventually end up with a rupture. In the few cases reported in literature, different operative techniques have been described, all with excellent results. A case of an initially overlooked dynamic dislocation of the PLT due to IPR tear in a young professional soccer player is described. The lesion was treated with a not yet described operative technique that consists in groove deepening and subsequent IPR repair through transosseous sutures, instead of peroneal tubercle resection as mostly advocated. Final follow up at 15 months showed complete recovery, with a Foot and Ankle Outcome Score of 100%.